2021
DOI: 10.1111/cea.14065
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Asian chronic rhinosinusitis in the era of type 2 biologics

Abstract: Chronic rhinosinusitis (CRS) is defined as the inflammation of the mucosa of the nose and paranasal sinuses over 12 weeks, occurring in 11%-12% of adults in Europe and the United States, 1 and approximately 8% of adults in China and Korea. 2,3 CRS frequently presents with other inflammatory airway conditions such as asthma and allergic rhinitis (AR), and imposes huge global health and economic burdens. 1,2 CRS is a highly heterogeneous disorder with diverse inflammatory profiles. [4][5][6] Based on endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 111 publications
(381 reference statements)
0
39
0
Order By: Relevance
“…The same trend was reported in previous studies conducted in China. 43 EETosis is known to be the basis of CLCs, which are found at the site of eosinophil infiltration and promote neutrophilic inflammation as well as NETosis. 16 44 45 This is a possible explanation of why most patients with severe type 2 CRS show mixed neutrophilic-eosinophilic inflammation, and the formation of NETs ultimately aggravates type 2 inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was reported in previous studies conducted in China. 43 EETosis is known to be the basis of CLCs, which are found at the site of eosinophil infiltration and promote neutrophilic inflammation as well as NETosis. 16 44 45 This is a possible explanation of why most patients with severe type 2 CRS show mixed neutrophilic-eosinophilic inflammation, and the formation of NETs ultimately aggravates type 2 inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Studies in Asia reported that the prevalence of severe type 2 CRS was generally less than 10% (4.4%–11.2%), and our results are similar to those of previous studies. 28 43 When investigating mixed eosinophilic-neutrophilic CRS in Asia, it is necessary to find causes of mixed inflammation other than autocrystallized CLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic differences in endotypes affected the clinical characteristics of patients with CRSwNP (Table 1). In Asian CRSwNPs, the prevalence of eosinophilic or type 2 inflammation is relatively lower and the burden of inflammation is less than Western CRSwNPs [32]. Also, the incidence of comorbidities such as asthma or AERD/NERD is low.…”
Section: Differences In Endotypes Between Asian and Western Countriesmentioning
confidence: 99%
“…There are potential targets for other cytokines and nontype 2 inflammation in CRS [32]. A clinical trial with biologics for epithelial cell-derived cytokines, including thymic stromal lymphopoietin and IL-33, is underway.…”
Section: Tailored Management In Asian Crswnpmentioning
confidence: 99%
“…New therapeutic strategies, such as biologics or reboot surgery, were introduced as a response to treat the recalcitrant nature of severe type 2 CRSwNP, which often shows a poor response to traditional treatment. The prevalence of type 2 inflammation in CRSwNP and severe type 2 inflammation related to severe infiltration of eosinophils and neutrophils with staphylococcal enterotoxin-specific immunoglobulin E in Asian population is below 50% and 4.4%–11.2%, respectively [ 3 ], much lower than in Western populations [ 4 ]. In addition, a study proposed that the response of type 2 CRSwNP to surgery is very much different from that of non-type 2 CRSwNP [ 5 ], and as a result, the role of biologics in treating CRSwNP in Asian populations seemed to be limited.…”
mentioning
confidence: 99%